Doktrin Roh Kudus (Pneumatologi) - Nita Viola; Tia Messiani; Yolanda Meliyani Br Surbakti; Sarmauli (CV Edujavare Publishing, 2025)
The Holy Spirit, as part of the doctrine of the Trinity, plays a vital role in the life of believers and is one of the central topics in Christian theology. As the third Person of the Trinity, the Holy Spirit functions as a Comforter, a Guide, and the Giver of spiritual gifts. However, understanding of the Holy Spirit often leads to theological disputes and misunderstandings in church practice. This study aims to provide a more comprehensive and systematic understanding of the doctrine of the Holy Spirit through a biblical approach, contextual analysis of the contemporary church, and practical application in ministry and spiritual formation. By highlighting the lack of deep theological understanding, the differences in perspectives among denominations, and the impact on the spiritual growth of congregations, this research offers strategies and guidance for the church to live more tangibly and balanced under the leading of the Holy Spirit. Through this study, it is expected that Christians will increasingly recognize the importance of the Holy Spirit's role in their personal lives, church communities, and missions amid the challenges of the present age.